2021
DOI: 10.1101/2021.11.08.467681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vitro reconstitution of divisome activation

Abstract: Bacterial cell division is coordinated by the Z-ring, a cytoskeletal structure of treadmilling filaments of FtsZ and their membrane anchors, FtsA and ZipA. For divisome maturation and initiation of constriction, the widely conserved actin-homolog FtsA plays a central role, as it links downstream cell division proteins in the membrane to the Z-ring in the cytoplasm. According to the current model, FtsA initiates cell constriction by switching from an inactive polymeric conformation to an active monomeric form, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…The difference may be explained by the higher stability of the cytoskeletal structures containing FtsA*, the longer residence time of filaments on the membrane making them less subject to redistribution by MinDE. It has already been reported that FtsZ and FtsA* recruit each other more efficiently to the membrane during filament formation 19 , and that the greater colocalization is mediated by FtsA* filaments having a higher packing density 19,47 . The finding that MinC did not further encourage the redistribution of FtsA*-anchored FtsZ is in agreement with in vivo data showing that FtsA* imparts resistance to high concentrations of MinC, which ordinarily disassembles the Z-ring 44 .…”
Section: Discussionmentioning
confidence: 95%
“…The difference may be explained by the higher stability of the cytoskeletal structures containing FtsA*, the longer residence time of filaments on the membrane making them less subject to redistribution by MinDE. It has already been reported that FtsZ and FtsA* recruit each other more efficiently to the membrane during filament formation 19 , and that the greater colocalization is mediated by FtsA* filaments having a higher packing density 19,47 . The finding that MinC did not further encourage the redistribution of FtsA*-anchored FtsZ is in agreement with in vivo data showing that FtsA* imparts resistance to high concentrations of MinC, which ordinarily disassembles the Z-ring 44 .…”
Section: Discussionmentioning
confidence: 95%